Generation of localized highly concentrated hydrogen peroxide clusters in water by X-rays. (3rd May 2020) - Ueno, Megumi; Nakanishi, Ikuo; Matsumoto, Ken-ichiro
Abstract: The formation of highly concentrated hydrogen peroxide (H2 O2 ) clusters (localized circumstance) in an aqueous solution during X-ray irradiation was demonstrated. The relationship between H2 O2 concentration and hydrogen donor-independent reduction of nitroxyl radicals was examined. The method to measure the distance between the clusters (localized circumstance) was assessed by comparing the simulation and the experimental results. Reaction mixtures containing a nitroxyl redox probe, 4-hydroxyl-2, 2, 6, 6-tetramethylpiperidine- N -oxyl (TEMPOL) and 3-carbamoyl-2, 2, 5, 5-tetramethylpyrrolidine- N -oxyl (CmP) at 0.1 mM were prepared containing several different concentrations (1.0 mM‒9.8 M) of H2 O2 . The reaction mixture was irradiated by 12000 μW/cm 2 UVB for 2 min, and reduction of the electron paramagnetic resonance (EPR) signal of the nitroxyl radicals was measured. An aliquot (2 µL) of 200 mM K3 [Fe(CN)6 ] or FeCl3 solution was added to 200 µL of the reaction mixture, and the time course of the EPR signal of the nitroxyl radicals was measured. To estimate the distance between the H2 O2 clusters, a series of nitroxyl radical solutions with several different concentrations (0.06 μM‒2.28 mM) was irradiated with X-rays, and the degree of reduction of nitroxyl radicals in each sample was measured. UVB, K3 [Fe(CN)6 ], or FeCl3 -induced EPR signal loss of the nitroxyl radicals was observed with H2 O2 concentrations greater than 10 mM or 100 mM, respectively. The EPR signal loss of nitroxyl radicals, TEMPOL or CmP, may occur in highly concentrated H2 O2 circumstances after oxidative stimulation. Plotting the X-ray-induced reduction of nitroxyl radicals versus their density revealed the high-concentration H2 O2 clusters to be separated by 40‒47 nm. Ionizing irradiation of an aqueous solution creates a localized highly concentrated H2 O2 environment.